Microfluidic Platforms to Unravel Mysteries of Alzheimer’s Disease: How Far Have We Come? - Pragya Prasanna; Shweta Rathee; Vedanabhatla Rahul; Debabrata Mandal; Macherla Sharath Chandra Goud; Pardeep Yadav; Susan Hawthorne; Ankur Sharma; Piyush Kumar Gupta; Shreesh Ojha; Niraj Kumar Jha; Chiara Villa; et al. (Life, 2021)
Alzheimer’s disease (AD) is a significant health concern with enormous social and economic impact globally. The gradual deterioration of cognitive functions and irreversible neuronal losses are primary features of the disease. Even after decades of research, most therapeutic options are merely symptomatic, and drugs in clinical practice present numerous side effects. Lack of effective diagnostic techniques prevents the early prognosis of disease, resulting in a gradual deterioration in the quality of life. Furthermore, the mechanism of cognitive impairment and AD pathophysiology is poorly understood. Microfluidics exploits different microscale properties of fluids to mimic environments on microfluidic chip-like devices. These miniature multichambered devices can be used to grow cells and 3D tissues in vitro, analyze cell-to-cell communication, decipher the roles of neural cells such as microglia, and gain insights into AD pathophysiology. This review focuses on the applications and impact of microfluidics on AD research. We discuss the technical challenges and possible solutions provided by this new cutting-edge technique to understand disease-associated pathways and mechanisms.